2016
DOI: 10.1002/gps.4513
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Mini‐Mental State Examination scores among urban community‐dwelling older adults in Japan

Abstract: The results of this study confirm that age and education affect MMSE scores. To ensure the effective use of the MMSE, it is recommended to examine scores corresponding to age and education. The normative data presented are expected to be useful for assessing MMSE scores in older individuals both in and out of the clinical setting. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 41 publications
7
24
1
Order By: Relevance
“…12 Therefore, in Japanese society with the largest percentage of people aged 65 or older, similar trends are observed to trends identified in studies from other countries. Concerning educational attainment, this study obtained similar results to a nationwide sample of an area-specific study in Japan.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…12 Therefore, in Japanese society with the largest percentage of people aged 65 or older, similar trends are observed to trends identified in studies from other countries. Concerning educational attainment, this study obtained similar results to a nationwide sample of an area-specific study in Japan.…”
Section: Discussionsupporting
confidence: 78%
“…[8][9][10][11][12] Occupation and complexity of work also reportedly affect cognitive functioning, 13-16 and living in a relationship with a partner and/or social network is associated with a lower risk of cognitive decline. [8][9][10][11][12] Occupation and complexity of work also reportedly affect cognitive functioning, 13-16 and living in a relationship with a partner and/or social network is associated with a lower risk of cognitive decline.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The association was significant ( r p  = 0.36, p  = 0.007), in accordance with previous studies, even with the consideration of confounding factors such as age, sex, and years of education. Behavioral data fit well with Japanese healthy age-matched normative data in MMSE55, FAB56, VFT, and WCST57. Unsurprisingly, EF-Z was significantly correlated with each separate index of EF (VFT: 0.61, FAB: 0.64, WCST (CA): 0.58, WCST (RT): −0.56, and KHT: 0.70; p < 0.001).…”
Section: Resultssupporting
confidence: 53%
“…However, a recent Japanese study [43] on community-dwelling older adults found a modest effect of sex with lower MMSE scores among women in the oldest age group. The sex difference in MMSE scores in our study is unlikely to be fully explained by differences in education, age, major depression or the number of days between the index attempt and the research interview.…”
Section: Discussionmentioning
confidence: 90%